Asthma, Food Allergy, and How They Relate to Each Other - Foong, Ru-Xin; du Toit, George; Fox, Adam T. (Frontiers in Pediatrics, 2017)
The association between atopic diseases is well known, and previous research has shown that having one atopic disease can predispose to having another. The link between asthma and food allergy has been well researched, but the exact relationship between the two atopic conditions is not fully understood. Food allergic infants are at increased risk for the development of asthma and are at risk of food-induced asthmatic episodes and also anaphylaxis. Having a diagnosis of both food allergy and asthma has also been shown to have an effect on the severity of a patient’s disease including being at greater risk of severe asthmatic episodes. Therefore, understanding the relationship between these two conditions in order to treat and manage these children safely is crucial to clinicians.